Alteration of Carbohydrate Metabolism in Fusarium Infected Wheat Kernels Treated with Fungicides and Its Relation to Baking Technological Parameters and Deoxynivalenol Contamination - Ács Katalin; Varga Mónika; Szekeres András; Salgó András; Lantos Csaba; Békés Ferenc; Pauk János; Mesterházy Ákos (2023)
Changes of water-soluble carbohydrate (WSC) content such as fructose, glucose, sucrose, maltose, nystose, raffinose, stachyose and fructan were analyzed in wheat kernels in Fusarium epidemic and non-epidemic seasons. In both season types, eight commercial fungicides were applied and three wheat varieties with differing Fusarium resistance were tested. In the epidemic year, the average total amount of WSC was above 1.6% which was 2 times higher than in the non-epidemic year (0.7%). Sucrose, maltose, raffinose and fructan components determined the increased WSC value, but the most substantial change was observed in maltose content where its average amount was 28 times higher in the epidemic year. Fungicide application also significantly increased all the carbohydrate components except maltose, where significant reduction was observed. WSC components had strong correlation with several farinograph or extensograph parameters, but only the maltose content showed positive strong correlation (r = 0.9) with deoxynivalenol (DON) toxin that was highly affected by the applied fungicide. The changes of WSC indicate altered carbohydrate synthesis along with abnormal degradation processes and thus have impaction on the baking features. It seems that the sugar metabolism interacts with DON synthesis and the results give important additional information to the altered metabolism of the attacked plant.
Keywords: Biológiai tudományok; Mezőgazdasági biotechnológia